Prof. N. N. Glubokovsky on “Stauropegia” in the Church (Notes from Sofia Archive) (Forum Theologicum Sardicense, 2025)
The topic of the stauropegial institute in the Church is as debatable today as it was in the 1920s. Many researchers believe this phenomenon is unfamiliar to the Church due to its canonical uncertainty. Professor Glubokovski’s opinion on this matter reflects his deep belief in the canonical dynamics of the Church, particularly regarding its structure and governance, while maintaining its eternal principles—i.e., the basic dogmas of the faith that are eternal and unalterable. There is no dispute that stavropigia does not contradict Scripture, Ecumenical Council decisions, or the historical and liturgical life of the Church. On the contrary, it is supported by these sources, which affirm its necessity and usefulness. Following Professor Glubokovski’s example, I believe this issue requires comprehensive and in-depth research to fully understand the stance of the Church, both in the East and the West.